DOUBLE LEG SPEED HOP AND HALF SQUAT JUMP IMPROVE LEG MUSCLE POWER - Wiratama, Gede Aditya (Sport and Fitness Journal, 2021)
Leg muscle explosiveness is one of the factors that determine the stability of jumping techniques in football. This research aims to prove that the combined training of Double Leg Speed ??Hop and Half Squat Jump is better than the Hurdle Jump in increasing leg muscle explosive power in male students participating in extracurricular football at SMP Negeri 2 Kuta Utara. Type of this research was true experimental with randomized pre and post-test with control group design. The research subjects were 18 male extracurricular football students at SMP Negeri 2 Kuta Utara which were divided into two different treatment groups. Treatment group was given training in a combination of Double Leg Speed ??Hop and Half Squat Jump and control group was given hurdles training, with a frequency of training 3 times a week for 6 weeks. Measurement of leg muscle strength measured using a meter board with a vertical jump test. The results of the study in both groups obtained the average leg muscle explosive power before training in the combination of Double Leg Speed ??Hop and Half Squat Jump 38.49 ± 4.658 cm, while after training the combination of Double Leg Speed ??Hop and Half Squat Jump became 48.17 ± 4.305 cm. The average explosive power of leg muscles before the Skipping Jump training was 36.63 ± 3.953 cm, while after the skipping jump training was 40.79 ± 4.227 cm. The mean difference test in the increased leg muscle power in treatment group and control group using independent t-tests in the post-test data of the two groups showed that p = 0.00 (p <0.05). It was concluded that the exercises in Treatment Group and Control Group both had an increased effect and in Treatment Group increased leg muscle power more than in Control Group. This research suggestions are expected to coaches can provide training properly and use evaluation monitoring improves athlete achievement. Keywords: Leg Muscle Explosive Power; Double Leg Speed ??Hop; Half Squat Jump; Hurdles Jumping; Football Extracurricular Boys SMP N 2 Kuta Utara